Cytotoxic Effect of Diols, Amides and Their Mixtures on Fowl and Turkey Sperm Prior to Freezing - Linnik, T. P.; Martynyuk, I. N.; Gaviley, O. V.; Beletsky, E. M. (Problems of Cryobiology and Cryomedicine, 2009)
There was studied the cytotoxicity of substances from amides’ and diols’ series (three representatives from each) in respect to the fowl and turkey spermatozoa at a preparative stage to freezing. It was shown, that the lowest damaging effect on fowl spermatozoa was observed in the presence of dimethylformamide (DMFA) and DMFA + 2,3-buthane diol (2,3-BD) mixture and for turkey spermatozoa was ethylene glycol (EG) and DMFA+EG, correspondingly.